2021
DOI: 10.3389/fnut.2021.756730
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids Alleviate Hepatocyte Apoptosis Induced by Gut-Derived Protein-Bound Uremic Toxins

Abstract: Chronic kidney disease (CKD) is characterized with the influx of uremic toxins, which impairs the gut microbiome by decreasing beneficial bacteria that produce short-chain fatty acids (SCFAs) and increasing harmful bacteria that produce gut-derived protein-bound uremic toxins (PBUTs). This study aimed to assess the proapoptotic effects of three major gut-derived PBUTs in hepatocytes, and the effects of SCFAs on apoptosis phenotype in vitro. HepG2 (human liver carcinoma cells) and THLE-2 (immortalized human nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 52 publications
1
15
0
1
Order By: Relevance
“…Similarly, phytosphingosine was found to induce carcinoma cell apoptosis . Furthermore, we concentrated on an interesting metabolite, hippuric acid, which is a common intestinal metabolite that can induce apoptosis . These further confirmed the implication of ERS-mediated apoptosis in the mechanism.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, phytosphingosine was found to induce carcinoma cell apoptosis . Furthermore, we concentrated on an interesting metabolite, hippuric acid, which is a common intestinal metabolite that can induce apoptosis . These further confirmed the implication of ERS-mediated apoptosis in the mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…46 Furthermore, we concentrated on an interesting metabolite, hippuric acid, which is a common intestinal metabolite that can induce apoptosis. 47 These further confirmed the implication of ERS-mediated apoptosis in the mechanism. What is more, it is exciting that a testosteronerelated substance named methyltestosterone was found.…”
Section: Discussionmentioning
confidence: 55%
“…Short-chain fatty acids (SCFAs) are generated in the colon by the fermentation of dietary fiber by gut microbiota. Hepatocytes can utilize SCFAs as a source of energy, which can lower glucose production by the liver and enhance insulin sensitivity ( 39 , 40 ). SCFAs can also stimulate the secretion of intestinal hormones, including glucagon-like peptide-1 (GLP-1), which can further enhance insulin secretion and improve glucose metabolism ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that the concentrations of SCFAs, especially acetic acid and butyric acid, were significantly reduced in CKD. However, improved intestinal barrier and renal function were observed through the supplementation of SCFAs, especially butyric acid ( Deng et al, 2021 ). Previous studies indicated that the alleviation of renal dysfunction was related to the improved SCFA concentrations and intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%